Potential Analysis Of Gawar Gong Ecotourism In Wanasaba District, East Lombok Regency: Development Environmental Learning Posters - Abidatul Muthiah; R. Didi Kuswara; Ahmad Fadli (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2020)
The purpose of this study was to determine the potential of GawarGong ecotourism in Otak Kebon, Beririjarak Village, East Lombokas a material for developing environmental learning posters. Thistype of research is research and development. Development researchis adapted from the 4D development model, namely through thestages of defining, designing, developing, and distributing. The dataanalysis used is descriptive qualitative analysis and SWOT analysis,namely the analysis of strengths, weaknesses, opportunities andthreats. The results showed that Gawar Gong ecotourism has a lot ofpotential such as natural beauty and flora and fauna that must bepreserved and preserved and the results of the validation test on thedeveloped posters show that environmental learning posters get avery feasible category value or can be used as an environmentallearning medium for the community and Gawar Gong ecotourismvisitors.